(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Lipids are of one of the four basic types of molecules of life and its derivatives serve diverse functions in the body. Generally acclaimed functions of lipids include shock absorption and insulation, and energy storage of the body. Phospholipids and cholesterol form the integral part of cell membrane. In addition cholesterol serves as the precursor for bile salts, male and female sex hormones, vitamin D and adrenocortical hormones. Complex lipids consist of neutral lipid core of cholesterol esters and or triacylglycerol and proteins are the chylomicrons, VLDL, LDL and HDL which serve as the carriers of fats, fatty acids and other lipids in the body. Complex lipids are tightly controlled in the body. Its dysregulation has been mainly linked to obesity, diabetes and insulin resistance though the issue is yet to be clearly understood. The present review evaluates recent reports in this regards and try to explain the relationship between dyspidemia and insulin resistance. DOI: http://dx.doi.org/10.3329/bjmb.v7i1.18576 Bangladesh J Med Biochem 2014; 7(1): 27-31